Predicting therapeutic outcome in severe ulcerative colitis by measuring in vitro steroid sensitivity of proliferating peripheral blood lymphocytes. Issue 3 (1st September 1999) - Hearing, S D; Norman, M; Probert, C S J; Haslam, N; Dayan, C M
Abstract : BACKGROUND: Up to 29% of patients with severe ulcerative colitis (UC) fail to respond to steroid treatment and require surgery. Previous studies have failed to show a clear correlation between failure of steroid treatment in severe UC and measures of disease severity. The reasons for treatment failure therefore remain unknown. AIM: To investigate the hypothesis that patients with severe UC who fail to respond to steroid treatment have steroid resistant T lymphocytes. METHODS: Eighteen patients with severe UC were studied. After seven days' treatment with high dose intravenous steroids they were classified as complete responders (CR), incomplete responders (IR), or treatment failures (TF). Within 48 hours of admission blood was taken and the antiproliferative effect of dexamethasone on phytohaemagglutinin stimulated peripheral blood T lymphocytes was measured. Maximum dexamethasone induced inhibition of proliferation (Imax ) was measured. RESULTS: In vitro T lymphocyte steroid sensitivity of TF and IR patients was significantly less than that of CR patients. Both TF and 3/5 IR patients had an Imax of less than 60%; all CR patients had an Imax of greater than 60%. No significant correlation was seen between response to treatment and disease severity on admission. When in vitro T lymphocyte steroid sensitivity was remeasured three months later, there was no difference between the groups. CONCLUSIONS: Results suggest that T lymphocyte steroid resistance is an important factor in determining response to steroid treatment in patients with severe UC and may be more predictive of outcome than disease severity.